A study on breakdown properties of coconut oil - Dung, Nguyen Van; Trung, Nguyen Hoai (Vietnam Journal of Science and Technology, 2019)
This paper presents the results of electric breakdown properties of coconut oil with AC voltage. Experimental results show that breakdown voltage of new coconut oil is comparable to that of mineral oil. Ageing was seen to significantly affect the breakdown voltage of both coconut oil and mineral oil. However, influence extent of ageing on the breakdown voltage was higher for mineral oil. The antioxidant was seen to reduce the breakdown voltage of new coconut oil, but raised the breakdown voltage of aged coconut oil. The V-t characteristic of coconut oil is not as good as that of mineral oil.